2014
DOI: 10.7763/ijiet.2014.v4.411
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Job Stress on Job Attitudes and Life Satisfaction in College Lecturers

Abstract: Abstract-The main objective of this study was to find out the relationship of job stress with job attitudes in college lecturers. This is a cross-sectional study design based on purposive sampling technique. The results revealed that job stress has a significant negative relationship with job performance, job satisfaction, and life satisfaction while positively significant related with turnover intentions. Further a significant difference was found among married and unmarried college lecturers on these study v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
2
17
0
3
Order By: Relevance
“…High turnover becomes a loss for organization's cost and profitability (Hassan, 2014). Khan, Aqeel, and Riaz (2014) noted that when a person suffers from mental and physical illness because of the unwanted settings, the situation is known as stressed. He also noted that there are many types of stressors, namely noise, dim light at working place, high job demands, role overload, role ambiguity, lack of sleep and time pressure, and everyday workload, contradictory demands, insufficient resources to perform well, inability to make decisions, and conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…High turnover becomes a loss for organization's cost and profitability (Hassan, 2014). Khan, Aqeel, and Riaz (2014) noted that when a person suffers from mental and physical illness because of the unwanted settings, the situation is known as stressed. He also noted that there are many types of stressors, namely noise, dim light at working place, high job demands, role overload, role ambiguity, lack of sleep and time pressure, and everyday workload, contradictory demands, insufficient resources to perform well, inability to make decisions, and conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…They also have to deal with functions outside the academic setting: their family life, social life and other commitments. Given the numerous roles and responsibilities, the intense demands and the high expectations set to them, many university faculty experience significant levels of stress and have shown particular responses to stress, such as increased turnover intent, decreased job performance, decreased job satisfaction, increased anxiety and increased depression (Reevy & Deason, 2014;Winefield & Jarrett, 2001;Blix, Cruise, Mitchell, & Blix, 1994;Veena, Pushpalatha, & Mallaiah, 2016;Khan, Aqeel, & Riaz, 2014).…”
Section: Faculty Stressmentioning
confidence: 99%
“…Stress can affect employee satisfaction levels which results in lower performance. Most studies that have linked work stress with lower job satisfaction identified a negative relationship between the two (Khan et. al., 2014;Bemana, et.…”
Section: Work Stress and Job Satisfactionmentioning
confidence: 99%